Aluminum-carbon nanotube nanocomposite for silicon solar cell back metallization - El-Rafei, Kareem (AUC Knowledge Fountain, 2015)
With the global push towards having thinner silicon solar cells, the bowing problem arising from the thermal mismatch between the Aluminum electrode and the Silicon wafer in the cell becomes more critical. The thinner the cells the more the bowing and the higher the probability of cracking and hence yield losses and lower cell efficiency. The main objective of this work was to explore the effect of introducing CNT into the composition of the Al paste in order to reduce the Coefficient of Thermal Expansion (CTE) of the resulting composite and hence reduce the bowing problem. Two types of samples were produced: Cylindrical and Wafer samples. The first consisted of 26 compacted and sintered at 500oC powders of the following consistencies: Un-Milled Al, Milled Al, 2%, 5% and 10% CNT-Al. CTE was measured by a Dilatometer DIL 801, TA instruments device. Electrical Performance was measured for the same samples via varying the voltage and measuring the current, then calculated the resistance taking the latter as an indicator for the Resistivity. In both tests, it was found that the 10% CNT-Al samples gave the highest results: in terms of CTE, it resulted in around 20% reduction, and in case of electrical performance, it increased the resistivity by around 3.8%. For the wafer samples, Un-Milled Al, Milled Al and 10% CNT-Al powder-based pastes were prepared using a patented recipe that was modified for the current work, and then the pastes were printed using Spin Coating technique on 9 wafers which were heated at 160oC for around 3 hours. A Contactless Wafer Geometry Gauge device was used to measure the bow and warp. Bow results were inconclusive, however the warping revealed promising results as it was clearly shown that the 10% CNT-Al paste caused the lowest warp per unit thickness of paste printed, average warp to Al paste layer thickness ratios for all 3 pastes were 0.59, 0.35 and 0.24 for the Un-Milled Al, Milled Al and 10% CNT-Al pastes respectively. SEM images of the Top & cross-sectional views of the wafer showed that while the Un-Milled Al and 10% CNT-Al wafers provided an almost uniform layer, the thickness of the layer of the Milled Al paste was relatively irregular due to employing irregular techniques of printing and un-even powder particle size.